Factores asociados a la tuberculosis pulmonar en adultos, la Libertad 2023” - Murillo Rojas , Kimberlyn Julissa (2024)
Pulmonary tuberculosis (TB), an infectious disease mainly caused by Mycobacterium tuberculosis, remains a global public health challenge. This study was dedicated to examining the risk factors linked to pulmonary tuberculosis in the adult population served at the Venus de Valdivia 2023 Health Center. To analyze the factors associated with pulmonary tuberculosis in adults belonging to the La Libertad canton, in the Salud Venus de Valdivia during the year 2023, to contribute to the promotion of the prevention and health of tuberculosis, thus contributing to the reduction of contagion and the burden of the disease in the adult population. The methods considered were observation, for a detailed and contextual understanding of risk factors in the natural environment of individuals; the inductive method, to generate theories from observed data; and the deductive, to test pre-existing hypotheses about the risk factors for tuberculosis. The analytical method was useful for breaking down complex data into simpler components, facilitating deeper understanding, and the synthesis method allowed different pieces of information to be combined to form a complete picture of risk factors. The purpose of this research project was to identify and analyze the factors associated with pulmonary tuberculosis in adults in the canton of La Libertad during the year 2023, through the study of sociodemographic, environmental and lifestyle variables, as well as the barriers in the access to health services, in order to provide evidence-based recommendations for the design of policies and intervention strategies that contribute to the prevention and effective control of this disease in the community